The association between ozone exposure and blood pressure in a general Chinese middle-aged and older population: a large-scale repeated-measurement study - Chen Tang; Yiqin Zhang; Jingping Yi; Zhonghua Lu; Xianfa Xuan; Hanxiang Jiang; Dongbei Guo; Hanyu Xiang; Ting Wu; Jianhua Yan; Siyu Zhang; Yuxin Wang; et al. (BMC Medicine)
Abstract Background The relationship between ozone (O3) exposure and blood pressure (BP) remains inconclusive. Given the scarcity of Chinese epidemiological data, more research on this association is of paramount importance, particularly among middle-aged and older Chinese populations. Methods This study involved 10,875 participants (median age: 60.0 years) in Xiamen, China, from 2013 to 2019, with 34,939 repeated BP measurements. Air pollutant exposure data, including O3, particulate matter, nitrogen dioxide, sulfur dioxide, and carbon monoxide were derived from China High Air Pollutants and High-resolution Air Quality Reanalysis datasets using a k-nearest neighbor algorithm. The relationship between mixed air pollutant exposure and BP was evaluated using Bayesian kernel machine regression model. The effects of daily-specific O3 exposure on BP were assessed by distributed lag models integrated into a linear mixed-effects framework. The mediating role of total cholesterol (TC), serum total bilirubin (STB), triglyceride (TG), and low-density lipoprotein (LDL) were examined using multilevel mediation analysis with a fully adjusted model. Results Mixed air pollutant exposure was positively correlated with BP, with O3 being a predominant contributor exhibiting an inverse effect. O3 exposure had immediate effects on pulse pressure (PP), while systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) showed delayed responses, with 3-, 14-, and 8-day lags, respectively. During the study period of up to 30 days, each 10 μg/m3 increase in maximum daily 8-h average O3 concentration was associated with reductions in SBP (β =  − 1.176 mm Hg), DBP (− 0.237 mm Hg), PP (β =  − 0.973 mm Hg), and MAP (β =  − 0.544 mm Hg). Stronger correlations were observed in the older participants (aged ≥ 65 years), overweight/obese individuals, smokers and alcohol consumers, and those with hypertension or type 2 diabetes mellitus. STB and LDL mediated these effects, while TC and TG played mitigating roles. Conclusions Short-term O3 exposure is negatively associated with BP in middle-aged and older Chinese individuals. The findings provide preliminary evidence for the impact of O3 exposure on BP regulation and underscore the urgent need to reassess public health policies in response to O3 pollution.